PENINGKATAN KETERAMPILAN GURU SEKOLAH DASAR DALAM PENAYANGAN VIDEO PADA MICROSOFT POWERPOINT DENGAN TEKNIK HYPERLINK - Usman Sutisna; Mia Fitriah Elkarimah (RANGKIANG: Jurnal Pengabdian Pada Masyarakat, 2020)
In the DKI Jakarta area, in the 2019/2020 school year it is almost certain that all schools in the Ministry of Education and Culture and the DKI Jakarta Education Office have compiled the 2013 curriculum. How to understand this 2013 curriculum encourages teachers to improve their quality and professionalism as educators adjusted to the needs of the present . The thing that is highlighted the most is the ability of a teacher in information technology literacy that is good at accessing and using the technology itself. At the same time in Menteng Atas Elementary School 02 Morning, there are still not a few teachers who have not mastered specific information technology in order to make IT-based learning media, therefore related to the team from Unindra will help community service to help teachers in doing communication 2013 (kurtilas) one of them with the help of teachers in providing learning using video media in PowerPoint with hyperlink techniques. Hopefully with community service activities we can help in developing and improving the professionalism of teachers in the field of information technology.